Coherence Alarm Implementation upon Post-Blast Impact in Open-Pit Mine - Muhammad Adib Izzuddin; Alden Sinai Yudono; Deaz Dewantara (Himpunan Ahli Teknik Tanah Indonesia, 2023)
Slope Stability Radar (SSR) is a geotechnical monitoring tool, an array of sophisticated technology which is equipped with features that could be utilized in dynamic mining conditions. One of the features is called coherence and is used to track the impact of blasting activity around the research area. Historically, it has been recorded that fall-of-ground event (bench-scale failure) had occurred after blasting activity around the research area. These two events were recorded perfectly by utilizing coherence attribute measurement, including the time of event and the dimension of the impact area. Therefore, the application of a coherence alarm could be one of the solutions to provide an immediate response to track the blasting impact and provide periodic notification in case of the similar things occurred in the future. There are two alarm parameters in which required some adjustments due to the sensitivity of coherence attribute. The first one, is the alarm mask. It masks out the expected unwanted triggering alarm, such as vegetation area, ramp, machinery area, and mining infrastructures. The second one is the alarm threshold. It requires precise adjustment to maximize the alarm function during the rainfall event. The analysis resulting the threshold values advocated for the alarm are 12 contiguous pixels, 2 scans, and 0.6 coherence value. The alarm configuration parameters are then applied to the coherence alarm system. Notwithstanding that matter, the alarm configuration requires periodic adjustments, accompanied by the competencies of the person in charge for the SSR to be able to comprehensively understand the concept of coherence and its implementation in the research area.